Review on physiological and ecological characteristics and agronomic regulatory pathways of intercropping to delay root and canopy senescence of crops - Wen Yin; Qiang Chai; Zhilong Fan; Falong Hu; Lianhao Zhao; Hong Fan; Wei He; Cai Zhao; Aizhong Yu; Yali Sun; Feng Wang (Journal of Integrative Agriculture, 2025)
Intercropping has been widely used in arid and semi-arid regions because of its high yield, stable productivity, and efficient utilization of resources. However, in recent years, the high yield of traditional intercropping is mainly attributed to the large amount of purchased resources such as water and fertilizer, plastic film, and mechanical power. These lead to a decline in cultivated land quality and exacerbate intercrops’ premature root and canopy senescence. So, the application of traditional intercropping faces major challenges in crop production. This paper analyzes the manifestations, occurrence mechanisms, and agronomic regulatory pathways of crop senescence. The physiological and ecological characteristics of intercropping to delay root and canopy senescence of crops are reviewed in this paper. The main agronomic regulatory pathways of intercropping to delay root and canopy senescence of crops are based on above- and blow-ground interactions, including collocation of crop varieties, spatial arrangement, water and fertilizer management, and tillage and mulch practices. Future research fields of intercropping to delay root and canopy senescence should focus on the aspects of selecting and breeding special varieties, application of molecular biology techniques, and developing or applying models to predict and evaluate the root and canopy senescence process of intercrops. Comprehensive analysis and evaluation of different research results could provide a basis for enhancing intercropping delay root and canopy senescence through adopting innovative technologies for regulating the physio-ecological characteristics of intercrops. This would support developing and adopting high-yield, efficient, and sustainable intercropping systems in arid and semi-arid areas with high population density, limited land, and abundant light and heat resources.